TATHWIR ADAWAT IKHTIBAR MAHARAH AL-QIRAAH BI ISTI'MAL KAHOOT FI AL-MADRASAH AL-TSANAWIYAH AL-HUKUMIYAH BI SUMATRA AL-GHARBIYAH - Rahmawati, Rahmawati; Mahesa, Jaka Imam (Arabi : Journal of Arabic Studies, 2019)
This research aimed to make or produce reading skills test tool using Kahoot platform. This was a "research and development" model using the 4D model (defines, designs, develops, determinates), yet this research was only up to the developing stage. The result of the development in this research is that the researcher developed the reading skills test questions using the Kahoot platform. These questions are written on the platform, then a picture is inserted in the question, as well as the answer choices and the correct answer. The picture helps students to understand the commands of the questions and the researcher used one type of question, the quiz, which is a question by providing answer choices from A to D. The answer choices in this problem are in the form of triangles, squares, circles and squares that have been rotated.  The students used the smart phone.  In this online test, the educator determined the time to answer the question.